“EFFECT OF TEMPERATURE VARIATION ON LEUTINISING HORMONE, FOLLICLE STIMULATING HORMONE AND CORTISOL HORMONE DURING VARIOUS STAGES OF REPRODUCTION IN CHHOTANAGPURI EWE” (Indian Journal of Animal Production and Management, 2013)
The present study was carried out to see the effect of different housing system on 24 non-pregnant healthy Chhotanagpuri ewes which were allocated equally to three different groups. Animals of group I were kept between the temperature range of 350C to 400C in intensive system in hot and humid condition, animals of group II were kept under intensive system between 200C-270C and animals of group III were kept under extensive system and served as control. The ewes allotted to different treatment groups were of nearly similar age and body weight. The physiological considerations like reproductive hormones LH, FSH and other important metabolic hormones like Cortisol plays vital role in regulating the reproductive efficiency. Therefore Plasma LH, plasma FSH and plasma Cortisol hormones concentration were estimated during the experimental period. The study revealed that the Plasma LH and plasma FSH concentration between different groups did not vary significantly (p
Keywords: Temperature; Luteinizing Hormone; Follicle Stimulating Hormone; Cortisol; Chhotanagpuri; Ewe